Late Paleozoic magmatism and foreland deformation associated with opening and closing of marginal basins in the North Patagonian Andes - C. W. Rapela; M. García; F. Hervé; R. J. Pankhurst; CALDERON NETTLE, MAURICIO ROBERTO; C. M. Fanning; S. O. Verdecchia (My University, 2024)
Remnants of coeval Devonian oceanic and continental foreland rocks are preserved in the basement of the North Patagonian Andes. Our previous studies of the igneous rocks here have shown that the primitive oceanic and continental igneous rocks are coeval and belong to a marginal basin that opened and closed over 50 Myr. A structural study and four new U–Pb SHRIMP ages and zircon Hf–O determinations allowed the identification of three metamorphic episodes, the first one of which, M 1 (D 1 -S 1 ), is coeval with Andean-type granite intrusion in the foreland (405–380 Ma). This activity was simultaneous with the development of an oceanic ridge and a marginal basin, at the outer edge of which a primitive granitic oceanic arc formed (380–385 Ma; zircon δ 18 O 3.6–5.2‰). The extinction of this ridge initiated under-thrusting of the oceanic crust below the continent and an important mid- to high-grade metamorphic event, M 2 (D 2 -S 2 ) at 375–360 Ma, its peak dated by metamorphic zircon rims in migmatite at 365 ± 3 Ma. Basin closure occurred after the intrusion of S-type granites (357 ± 2 Ma; zircon δ 18 O 7.4–10.4‰) in the foreland and the accretion of gabbros, cumulate gabbros and trondhjemites at the proto-Pacific margin. Compression prevailed for 20 Myr in the foreland, causing a mylonitic medium-grade M 3 (D 3 -S 3 ) event. Supplementary material: Datasets are available at https://doi.org/10.6084/m9.figshare.c.6989873